Maritime Delimitation of the Continental Shelf in Europe with special reference to the Mediterranean Sea - Swindells, Jenni (Institute of Marine and Environmental Law, 2021)
The purpose of this thesis is to examine the development of State practice, conventions, judicial decisions, arbitral awards, and settlements on the delimitation of maritime boundaries in a European and Mediterranean context. Conclusions will be expressed on important principles which may be of relevance in future, delimitations, not only in these areas but also more generally.